Effect of Rice Husk Ash and Cow Urine on The Growth And Yield of Kale on Peat Soil - lili yulianti (Jurnal Sains Pertanian Equator, 2021)
The research aims to determine the interaction of rice husk ash and cow urine in increasing growth and yield of kale on peat soil. The research lasted for 64 days starting on February 7 2020 – April 10 2020. The research was conducted in the experimental field of Agricultue Faculty of Tanjungpura University in Pontianak. The research used a completely randomized design (CRD) method consisting of 2 factors, namely rice husk ash and cow urine consisting of 3 levels of rice husk ash treatment and 3 level of cow urine, into 9 treatments, 3 replications and 4 sample plants, so there 108 plants. The treatment consis of a1 (450 g/polybag), a2 (569 g/polybag), a3 (678 g/polybag), u1 (20%), u2 (40%) and u3 (60%). The variables observed in the research number of leaves (sheet), plant fresh weight(g), root volume (cm3), plant dry weight (g), and root dry weight (g). The results showed that there was an interaction between rice husk ash and cow urine give a significant effect to the variables of root volume, plant dry weight and root dry weight. The best combination of giving rice husk ash and cow urine is a2u2 treatment, namely 569 g of rice husk ash and 40% cow urine.Keyword :Brassica oleraceae var.sabellica,cow urine, peat soil, rice husk ash